The Effect of Self efficacy and Compensation on Work Discipline in Improving Employee Performance in PDAM Tirta Mahameru in Lumajang District - Muhammad Riski Rama Duta; Markus Apriono; Sumani (ABM: International Journal of Administration, Business and Management, 2025)
Employee performance is a key variable in supporting the effectiveness of organizational operations, especially in the context of public services at PDAM Tirta Mahameru, Lumajang Regency. This study aims to analyze the effect of self-efficacy and compensation on employee performance with work discipline as a mediating variable. Self-efficacy is defined as an individual's belief in the ability to complete a task, while compensation includes remuneration, incentives, and facilities that function as employee motivators. This study uses a quantitative approach with a path analysis method on a population of 152 employees. Primary data were obtained through a Likert-scale questionnaire and analyzed using validity, reliability, and classical assumption tests. The results of the analysis show that self-efficacy and compensation significantly affect work discipline, which in turn has a positive effect on employee performance. In addition, self-efficacy and compensation also have a significant direct effect on employee performance. Mediation analysis indicates that work discipline acts as a partial mediator in the relationship between self-efficacy and performance, while the mediation of work discipline on the relationship between compensation and performance does not show a dominant role. This finding confirms that improving employee performance can be achieved through strengthening self-efficacy, optimizing the compensation system, and developing consistent work discipline in the PDAM Tirta Mahameru environment of Lumajang Regency.